Implementation of the CMIP6 Forcing Data in the IPSL‐CM6A‐LR Model. (15th April 2020) - Lurton, Thibaut; Balkanski, Yves; Bastrikov, Vladislav; Bekki, Slimane; Bopp, Laurent; Braconnot, Pascale; Brockmann, Patrick; Cadule, Patricia; Contoux, Camille; Cozic, Anne; Cugnet, David; Dufresne, Jean‐Louis; et al.
Abstract: The implementation of boundary conditions is a key aspect of climate simulations. We describe here how the Climate Model Intercomparison Project Phase 6 (CMIP6) forcing data sets have been processed and implemented in Version 6 of the Institut Pierre‐Simon Laplace (IPSL) climate model (IPSL‐CM6A‐LR) as used for CMIP6. Details peculiar to some of the Model Intercomparison Projects are also described. IPSL‐CM6A‐LR is run without interactive chemistry; thus, tropospheric and stratospheric aerosols as well as ozone have to be prescribed. We improved the aerosol interpolation procedure and highlight a new methodology to adjust the ozone vertical profile in a way that is consistent with the model dynamical state at the time step level. The corresponding instantaneous and effective radiative forcings have been estimated and are being presented where possible. Plain Language Summary: Climate Model Intercomparison Project Phase 6 is an international project to compare the results from climate model simulations performed according to a common protocol. Such simulations require boundary conditions (called "climate forcings"), which are fed to the models in order to represent, for example, long‐lived greenhouse gases, ozone, atmospheric aerosols, or land surface properties. The same forcing data sets are used by the different modeling groups who carry out the Climate Model Intercomparison Project Phase 6 simulations; however, their implementation may differ as it depends on the model structure. This article gives details of how these forcing data were implemented in the IPSL‐CM6A‐LR model. Some of the forcing data are common to all types all simulations, whereas others depend on the runs considered. Radiative forcings, as estimated in the model, are presented for some of the forcing mechanisms. Key Points: We present how the CMIP6 forcing data were implemented in the IPSL‐CM6A‐LR climate model for the realization of the CMIP6 set of climate simulations An improved conservative interpolation procedure for emissions is detailed and illustrated to compute tropospheric aerosols We present a new methodology to adjust the prescribed ozone vertical profile to match the model atmospheric dynamical state around the tropopause